Making sense of Men's Health: an investigation into the meanings men and women make of Men's Health - McCance-Price, Maris (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2006)
This study investigates the popular pleasures produced by readers of men's magazines, focusing primarily on the publication, Men's Health, which represents a new type of magazine catering for men. Using qualitative research methods such as textual analysis and reception analysis, the study explores the pleasures produced by both men and women from the consumption of such texts. The theoretical perspective of cultural studies informs this project, an approach that focuses on the generation and circulation of meanings in society. Focusing on the notion of the active audience and Hall's encoding/decoding model, this study examines readers' interpretations of the Men's Health text, focusing on the moment of consumption in the circuit of culture. Reception theory proposes the existence of "clustered readings" produced by interpretive communities that are socially rather than individually constructed. As a critical ethnography, the study interrogates these meanings with particular reference to questions of gender relations and power in society. Access to different discourses is structured by the social position of readers within relations of power and this study takes gender as a structuring principle. Therefore, this study also explores the particular discursive practices through which masculine and feminine imagery is produced by the Men's Health text and by its readers. The research findings support the more limited notion of the active audience espoused by theorists such as Hall (1980) offering further evidence to suggest that readers produce readings other than those preferred by the text and that therein lies the pleasure of the text for male and female readers. The research concludes that the popularity of Men's Health derives from the capacity of its readers to make multiple meanings of the text.
Keywords: Men's Health (South Africa); Men's magazines -- South Africa; Men in mass media; Women in mass media; Sex role in mass media; Men in popular culture; Women in popular culture; Mass media -- Social aspects